Gender and international climate policy: An analysis of progress in gender equality at COP21 - Huyer, Sophia (CGIAR Research Program on Climate Change, Agriculture and Food Security, 2016)
Sophia Huyer- Gender and Social Inclusion Research Leader of the CGIAR Climate Change, Agriculture and Food Security Programme (CCAFS).